2017
DOI: 10.1007/s11064-017-2362-1
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Regulation of Synaptic Function at Hippocampal TA-CA1 and SC-CA1 Synapses: Implications for Health and Disease

Abstract: Discovery of the obese (ob) gene in 1994 via positional cloning techniques enabled insight into the physiological system that controls body weight and energy expenditure [1]. Subsequent investigations identified the ob gene product as a 16 kDa protein that reduced food intake and increased energy expenditure in genetically obese (ob/ob) rodent models, indicating a pivotal role in regulating energy homeostasis. This protein was termed leptin [2,3].Leptin is primarily produced and secreted by white adipose tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 109 publications
0
24
0
Order By: Relevance
“…40,58 Leptin stimulates the JAK2-PI3K pathway in both presynaptic GABAergic terminals and postsynaptic POMC neurons. 61,62 In contrast to these mechanisms, we found that the voltage-sensitive potassium channel is the target of leptin in OB neurons. 60 In the hippocampus, leptin rapidly enhances NMDAinduced increases in intracellular Ca 2+ levels and facilitates NMDA currents, but not AMPA currents; the underlying signaling mechanism involves activation of phosphoinositide 3-kinase, mitogen-activated protein kinase, and Src tyrosine kinases.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…40,58 Leptin stimulates the JAK2-PI3K pathway in both presynaptic GABAergic terminals and postsynaptic POMC neurons. 61,62 In contrast to these mechanisms, we found that the voltage-sensitive potassium channel is the target of leptin in OB neurons. 60 In the hippocampus, leptin rapidly enhances NMDAinduced increases in intracellular Ca 2+ levels and facilitates NMDA currents, but not AMPA currents; the underlying signaling mechanism involves activation of phosphoinositide 3-kinase, mitogen-activated protein kinase, and Src tyrosine kinases.…”
Section: Discussionmentioning
confidence: 64%
“…60 In the hippocampus, leptin rapidly enhances NMDAinduced increases in intracellular Ca 2+ levels and facilitates NMDA currents, but not AMPA currents; the underlying signaling mechanism involves activation of phosphoinositide 3-kinase, mitogen-activated protein kinase, and Src tyrosine kinases. 61,62 In contrast to these mechanisms, we found that the voltage-sensitive potassium channel is the target of leptin in OB neurons. This important finding provides new information about how leptin interacts with neurons in the brain.…”
Section: Discussionmentioning
confidence: 64%
“…]). Moreover, the levels of two adiposeā€derived peptide hormones, leptin (the pleiotropic hormone of satiation signals/energy expenditure ) and resistin (the hormone that may ā€˜resistā€™ insulin actions ), were decreased to the same extent in F1 and F2 mice (Fig. ).…”
Section: Discussionmentioning
confidence: 96%
“…After NMDARmediated calcium influx to the cytoplasm, another glutamate receptor, Ī±-amino-3-hydroxy-5-methyl-4isoxazolepropionic acid (AMPAR), is transported from the Golgi apparatus to the cell membrane (Moult et al 2010). The transport of AMPAR exemplifies the principle of activity-dependent synaptic plasticity; LTP is mediated by AMPAR insertion into the membrane, whereas removal of AMPAR from the membrane mediates LDP (Collingridge et al 2004, McGregor & Harvey 2017.…”
Section: Leptin As a Key Player In Food Intake Regulation: A Role In mentioning
confidence: 99%